Mechanism Underlying Acupuncture Therapy in Spinal Cord Injury: A Narrative Overview of Preclinical Studies - Jiang, Kunpeng; Sun, Yulin; Chen, Xinle (Frontiers in Pharmacology, 2022)
Spinal cord injury (SCI) results from various pathogenic factors that destroy the normal structure and function of the spinal cord, subsequently causing sensory, motor, and autonomic nerve dysfunction. SCI is one of the most common causes of disability and death globally. It leads to severe physical and mental injury to patients and has a substantial economic burden on families and society. The pathological changes and underlying mechanisms within SCI involve oxidative stress, apoptosis, inflammation, etc. As a traditional therapy, acupuncture has a positive effect promoting the recovery of SCI. Acupuncture-induced neuroprotection includes several mechanisms such as reducing oxidative stress, inhibiting the inflammatory response and neuronal apoptosis, alleviating glial scar formation, promoting neural stem cell differentiation, and improving microcirculation within the injured area. Therefore, the recent studies exploring the mechanism of acupuncture therapy in SCI will help provide a theoretical basis for applying acupuncture and seeking a better treatment target and acupuncture approach for SCI patients.